2021
DOI: 10.1177/14613557211004621
|View full text |Cite
|
Sign up to set email alerts
|

Texas sheriffs’ perceptions on firearm regulations and mass shootings

Abstract: Criminal justice research often focuses exclusively on municipal police departments. Sheriffs’ departments are largely ignored in this research despite this population’s reach and role. There are nearly 3,000 sheriffs’ offices around the United States and they often serve as the only law enforcement body in rural areas. This study sought to address the scarcity of this research and focused on Texas sheriffs’ views regarding firearm regulations and the causes of mass shootings. An 18-question instrument created… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…These results bolster prior qualitative findings suggesting that personal and local politics may be a barrier to LEO uptake of ERPOs . Other research has similarly found that conservative law enforcement personnel are less likely to support firearm regulations …”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…These results bolster prior qualitative findings suggesting that personal and local politics may be a barrier to LEO uptake of ERPOs . Other research has similarly found that conservative law enforcement personnel are less likely to support firearm regulations …”
Section: Discussionsupporting
confidence: 75%
“…13 Other research has similarly found that conservative law enforcement personnel are less likely to support firearm regulations. 24 Training may also help dispel some of the misconceptions officers seem to have about when…”
Section: Discussionmentioning
confidence: 99%
“…These complexities of federalism are particularly relevant in the case of gun policy, as local variations in gun use, gun violence rates, and policy preferences mean that city and county governments bear unequal consequences of gun availability in the United States. While scholars have documented conflict in the top-down use of preemption by states in firearm policy (Riverstone-Newell 2017), we know considerably less about how and why local governments and elected officials may resist state and federal firearm policies (Meitl, Wellman and Kinkaid 2021). And while ideological mismatches between governments may drive federalism and policy, much less is known about how right-wing extremism efforts might shape cooperation (or the lack thereof) between local, state, and federal governments.…”
Section: Introductionmentioning
confidence: 99%
“…Criminal justice research often focuses on police departments (Decker, 1979). Research on sheriff departments remains scarce in comparison, despite the significant role sheriffs have in their respective counties (Except see: Meitl et al, 2020; Meitl et al, 2021; Hancock, 2019; Woldoff et al, 2017; Thompson et al, 2011). While there are no recent studies on Texas Sheriffs views of immigration, research suggests the more conservative a jurisdiction’s citizenry, the more likely they are to support limiting undocumented immigrants into their area and more likely to support removal efforts (Saad, 2010).…”
Section: Introductionmentioning
confidence: 99%